PENGARUH BRAND AMBASSADOR TERHADAP MINAT BELI PRODUK MOM UUNG - Anggraeni, Diana; Muctar, Shanon Riesva Natasya; Ahmad, Rosmalia (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
The importance of maternal and child health issues is the focus of sustainable development goals. In an effort to maintain the quality of mother's breast milk through booster products, Mom Uung will provide healthy babies. To reach it, you need the role of a brand ambassador so that breastfeeding mothers are interested in buying and using it. The aim of this research is to determine the influence of brand ambassador level on the level of buying interest of breastfeeding mothers who follow Mom Uung's Instagram account for products. This research uses the AIDA model, purchase intention, and brand ambassadorship as a basis for viewing the phenomenon from a theoretical and conceptual perspective. The research methodology uses a positivism paradigm with a quantitative approach. Meanwhile, this type of research is explanatory in nature to see the influence of brand ambassadors on interest in buying Mom Uung products by breastfeeding mothers as the unit of analysis. The sampling technique was purposive by attaching several criteria to respondents, in this case 100 breastfeeding mothers, obtained using the Slovin formula. Simple linear regression analysis is used as a data analysis technique. Research findings show that Nagita Slavina as the brand ambassador for Mom Uung products has a significant influence on the buying interest of breastfeeding mothers. In conclusion, there is an influence of brand ambassadors on purchasing interest. Therefore, it can be concluded that brand ambassadors influence consumer buying interest (breastfeeding mothers).